1989
DOI: 10.1073/pnas.86.19.7442
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the MYC gene amplified in human HL-60 cells after treatment with inhibitors of poly(ADP-ribose) polymerase or with dimethyl sulfoxide.

Abstract: In HL-60 cells, a human promyelocytic leukemia cell line, the human c-myc gene, designated MYC, is amplified about 16-fold. On differentiation of the HL-60 cells into granulocytes induced by several inhibitors of poly(ADPribose) polymerase [NAD' poly(adenosine diphosphate Dribose)ADP-D-ribosyltransferase, EC 2.4.2.30] including benzamide, nicotinamide, coumarin, and 4-hydroxyquinazoline or dimethyl sulfoxide, some MYC loss was observed. In contrast, benzoic acid, a noninhibitory analogue of benzamide, did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Previously, Shima et al observed a loss of c-MYC copies during treatment of HL-60 cells with DMSO and suggested this as a cause of differentiation (18). We reported that the spontaneous granulocytic differentiation of HL-60 cells that occurs without treatment with drugs was also associated with loss of c-MYC copies and it progressed at a similar slow rate as the DMSOinduced differentiation (19).…”
mentioning
confidence: 61%
“…Previously, Shima et al observed a loss of c-MYC copies during treatment of HL-60 cells with DMSO and suggested this as a cause of differentiation (18). We reported that the spontaneous granulocytic differentiation of HL-60 cells that occurs without treatment with drugs was also associated with loss of c-MYC copies and it progressed at a similar slow rate as the DMSOinduced differentiation (19).…”
mentioning
confidence: 61%
“…Exogenously introduced oncogenes, H-ras T24 , Ki-ras, N-ras, c-raf, and c-ret-II, in NIH 3T3 transformants were lost by treatment with PARP inhibitors (Nakayasu et al, 1988), and the endogenously amplified c-myc gene in HL-60 cells was also lost by a similar treatment (Shima et al, 1989). It is not clear yet whether dysfunction of PARP-1 is the sole cause, or whether other members of the PARP family, mentioned below, may also contribute to this phenomenon.…”
Section: Loss Of Amplified Genes and Deletion Mutationsmentioning
confidence: 95%
“…The HU treatment reduced the number of DMs in advanced ovarian carcinoma in vivo [Raymond et al, 2001]. The inhibitor of poly(ADP-ribose) polymerase or dimethyl sulfoxide also reduced the copy number of amplified c-myc in HL-60 cells [Shima et al, 1989]. Furthermore, ionizing radiation accelerated the loss of amplified MDR1 on DMs in multi-drug resistant KB cells [Sanchez et al, 1998;Schoenlein et al, 2003] or amplified c-myc in COLO 320DM cells [Schoenlein et al, 2003].…”
Section: An Active Mechanism May Eliminate Amplifiedmentioning
confidence: 99%